Characteristics of anesthetic management in elderly patients with frailty syndrome - O. A. Halushko; L. M. Zenkina (Zaporožskij Medicinskij Žurnal, 2025)
The increase in the proportion of elderly people has led to a proportional increase in geriatric patients undergoing surgical treatment. Elderly patients often develop geriatric syndromes, one of which is the frailty syndrome.